COMPARATIVE ASSESSMENT OF PATHOGENICITY AND CYTOPATHOGENICITY OF SELECTED PPRV STRAINS - L. Kutumbetov; B. Myrzakhmetova; G. Zhapparova; A. Tuyakov; T. Tlenchiyeva (Animal Health and Biosafety, 2026)
Peste des petits ruminants (PPR) is a major transboundary infection causing substantial economic losses in sheep and goat farming. Despite advances in molecular and epizootiological research, information on the biological properties of peste des petits ruminants virus (PPRV) remains limited, particularly regarding strain-related differences in pathogenicity, cytopathogenicity, and replication in different cell cultures. This study aimed to comparatively assess the virulence and in vitro biological properties of selected PPRV strains. A comparative phenotypic investigation of several PPRV strains was performed in lambs and goat kids, with monitoring of clinical course and outcome. In vitro, viral replication and cytopathic effect were evaluated in primary lamb and goat kidney cell cultures and in passaged cell lines, including the SKC cell line. PPRV strains showed marked differences in virulence in vivo, with subacute and acute forms leading to fatal outcomes, as well as subclinical infection. The strains varied in replication intensity and in the pattern of cell monolayer damage, with strain 45G showing the highest cytopathogenic activity, likely reflecting prior in vitro adaptation. Primary lamb and goat kidney cultures were the most sensitive to PPRV, whereas among passaged cell lines the SKC cell line provided consistently high virus yields and demonstrated practical value for virological and serological assays. The findings broaden current understanding of the biological properties of PPRV and highlight strain-dependent differences in virulence, cytopathogenicity, and cell culture susceptibility. The obtained data may support the optimization of diagnostic systems and experimental models for PPR. Further studies should focus on molecular characterization of strains with differing virulence and on the development of standardized sensitive cell systems for virus isolation, titration, and serological testing.